Nutrition education : linking research, theory, and practice - Contento, Isobel R.; Koch, Pamela A. (2021)
"Nutrition Education: Linking Research, Theory, and Practice provides a simple, straightforward model for designing effective nutrition education programs that address the personal and environmental influences affecting individuals' food choices and assists them in adopting healthy behaviors throughout their lifetime. Built around the six-step DESIGN process, the Fourth Edition integrates research, theory, and practice and provides advice and direction on designing, implementing, and evaluating theory-based nutrition education. This text is divided into three parts: Part I describes the key elements of success for nutrition education, as well as the major theories that can be used in nutrition education interventions. Part II features the 6-step process for designing nutrition education, translating theory into concrete objectives and strategies that can be practically implemented. It includes worksheets and case studies to provide a clear illustration of each step. Part III describes the nuts and bolts of implementing nutrition education, including information on leading groups, working with diverse populations, making presentations, and using media effectively"--
Includes bibliographical references and index.
Keywords: Nutrition -- Study and teaching; Dietetics -- education; Health Education -- methods; Food Habits; Health Behavior